Recovery of Capsaicinoids and Other Phytochemicals Involved With TRPV-1 Receptor to Re-valorize Chili Pepper Waste and Produce Nutraceuticals - Cortés-Ferré, Hector Emmanuel; Guajardo-Flores, Daniel; Romero-De La Vega, Gregorio; Gutierrez-Uribe, Janet Alejandra (Frontiers in Sustainable Food Systems, 2021)
The hot chili pepper industry represents one of the most important staple foods in Mexico and many Asian countries. Nowadays, large amounts of waste materials are produced from the pepper supply chain that could be used as a source to obtain nutraceuticals. Among the most common and important bioactive compounds contained in pepper residues are the capsaicinoids, which are the responsible of the pungency of the pepper. Capsaicinoids, mainly capsaicin, may ameliorate obesity, gastric disorder, diabetes, cardiovascular diseases, cancer, rhinitis, asthma, immune system diseases and important viral diseases as the recent COVID-19. The aim of this review is to review the industrial process for the extraction of capsaicinoids ingredients from pepper residues and to examine the relation of the capsaicin and other chili pepper phytochemicals to prevent and treat chronic diseases explained through the key role of the TRPV1 receptor. The extraction and incorporation of these compounds into nutraceutical formulations depend mainly on the development of new methods to improve not only the yield of a particular compound but the validation of the bioactivity and phytochemical characterization.